Productive and physiological performance and carcass quality of feed-restricted broilers offered diet supplemented with organic selenium and Iraqi protein concentrate 6×1 - Kareem, D. S.; Al-Shammari, K. I. A. (International Journal of Agricultural Technology, 2024)
Feed restriction (FR) regimes are reported as useful strategies in poultry feeding for economical and physiological considerations. From 1 to 5 weeks of broilers’ rearing, the current results revealed that most of the FR groups involving quantitative FR (40% of diet) or temporal FR (12 hours/day) without feed additive or with dietary supplementation of 0.8 mg organic selenium (OS) and 25 g Iraqi protein concentrate 6×1 (IPC) per kg decreased (p≤0.01) feed intake with no effect on body weight, weight gain, relative growth rate and feed efficiency in comparison to control. Also, both temporal FR with dietary OS and IPC were lowered a total mortality (p≤0.05), registered a high carcass yield with giblets (p≤0.05) and maintained a body massiveness. Low abdominal fat (p≤0.05) was found to favor of quantitative FR with dietary OS and IPC and temporal FR with dietary OS. All FR groups fed OS and IPC except for quantitative FR group differed from control in carcass length and bone lengths of keel, thigh and drumstick and circumferences of thigh and breast as well as breast compactness. Each FR group was significantly changed in serum metabolites such as total protein, total cholesterol, glucose, uric acid, creatinine, alanine transaminase and alanine transaminase at 3 and 5 weeks of age. The gizzard and small intestine pH at 3 weeks and large intestine pH at 6 weeks were all decreased (p≤0.05) by quantitative FR with dietary OS as compared to control. In conclusion, a beneficially special mechanism for each FR group especially those fed diet supplemented with OS and IPC was observed to induce a positive change or maintenance the investigated variables without any deleterious effects on broilers’ productivity